EP.TU.269Management of preoperative anemia with Iron Therapy in colorectal cancer patients- a Systematic Review and Meta-Analysis. (28th October 2021) - Narayanasamy, Sangara Narayanan; Gumber, Ashutosh; Kumar, Gautham; Aspari, Ajay Raghunath; Ramesh, Vibha; Thomas, Pradeep
Abstract: Background: Nearly half of colorectal cancer (CRC) patients are diagnosed with anemia at the initial assessment (Ferlay et al., 2015). Anemic patients require blood transfusion, which increases cancer recurrence (Acheson et al., 2012). Hence iron therapy for anemia correction reduces postoperative morbidity and mortality. Aims: To review randomized controlled trials on iron therapy for preoperative anemia in CRC patients. Methodology: Includes formulating a review question, analyzing, quantifying the inclusion and exclusion criteria, literature search, quality assessment, data extraction and data synthesis, bias rectification, results interpretation and summarizing the evidence. Cochrane Handbook of Systematic Reviews and acronym PICO has been used for formulating review questions and study design (O'Connor et al., 2011). Selection Criteria: Systematic reviews and RCTs with higher level of evidence were included in this review Data Extraction: Quality assessment and data collection were done using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta- Analysis) checklist. Data extraction and analysis done by REVMAN Manager (Higgins et al., 2011). Results: Two trials reported that iron therapy reduces the need for blood transfusion, but with insignificant result. All three studies showed that hemoglobin rise occurs with iron therapy postoperatively. None of the studies analyzed the quality of life. Recommendations: RCTs with larger sample size to be done for more relevant and accurate reports, aiming at the primary and secondary outcomes like morbidity, mortality and quality of life. Oral iron with fewer side effects has to be experimented for best efficacy.